(untitled) (Salud, Arte y Cuidado, 2025)
Hand hygiene is essential for reducing healthcare-related infections and ensuring patient safety in various healthcare settings. This report aims to describe the experience of ERE in learning about hand hygiene in nursing education. A guide for reporting educational interventions was used in a Brazilian higher education institution between April and May 2020. The design and implementation of the educational intervention were carried out voluntarily by 39 students, the majority of whom were female (72%). Although the students had access to a checklist of the appropriate steps for carrying out the procedure, only 70% performed it excellently. The creative and authorial production about learning the hand hygiene technique made it possible to understand the procedural content and value curiosity in the context of ERE, enabling the construction of educational processes supported by viable and feasible digital technologies after resuming face-to-face activities in nursing education.